Water-Cooled Radiofrequency: A Neuroablative or a Neuromodulatory Modality with Broader Applications? - Khalid Malik; Honorio T. Benzon; David Walega (Case Reports in Anesthesiology)
We report the successful use of water-cooled radiofrequency where more traditional forms of neuroablation—conventional and pulsed radiofrequency—had failed to achieve adequate pain relief. We also discuss the mechanism of neural damage with water cooled radiofrequency and discuss why this technique may have a broader role in the management of a wide array of pain syndromes.